An enhanced and provably secure multi-factor authentication scheme for Internet-of-Multimedia-Things environments. (December 2020) - Mahmood, Khalid; Akram, Waseem; Shafiq, Akasha; Altaf, Izwa; Lodhi, Muhammad Ali; Islam, SK Hafizul
Highlights: We have cryptanalyzed Dhillon and Karla's authentication protocol for IoMT environments and found that it is insecure against many attacks. We have designed a more secure remote user authentication protocol using elliptic curve for IoMT system. The proposed protocol is provably secure in the Random Oracle Model. The proposed protocol provides resistance against significant security attacks. The performance analysis proved that proposed protocol is more efficient than other competing protocols. Graphical abstract: Abstract: The Internet-of-Multimedia-Things (IoMT) opens new doors towards various contingencies to improve applications and services through efficient multimedia data usage. The ever-enlarging content of multimedia information in an IoT system makes it a critical security concern. Whenever users access services or information through a public channel, he/she is exposed to numerous security threats. Many security schemes have been introduced for IoMT environments to tackle the above-said concerns. Still, most of them do not fulfill all the security requirements of the IoMT systems. Recently, Dhillon and Karla have presented an authentication scheme for the IoMT environment. They have declared that the scheme is robust and can resist significant security attacks. However, we noticed that Dhillon and Kalra's scheme is susceptible to user masquerading attacks and a stolen verifier attack. Besides, their scheme also violates the anonymity and traceability of a user. This paper proposes a more secure remote user authentication scheme using the elliptic curve cryptosystem for the IoMT system. We have evaluated our scheme formally through the random oracle model. The informal security description proves that our scheme provides resistance against significant security attacks. Further, the performance analysis reveals that our scheme is more flexible, robust, and efficient than the relevant schemes.